(untitled) (Perioperaciina Medicina, 2019)
Introduction. Non-fermenting Gram-negative bacilli are known as one of the most frequent causative agents of hospital-acquired infections. Acinetobacter baumannii, as causative agent of infection complications of different localization, has obtained recently high resistance to anti-biotics and has belonged to ESKAPE group of pathogens. Antimicrobials, recommended for the prophylaxis and therapy of hospital-acquired infections, have been failing in their effectiveness and lead to selection of antibiotic resistant strains of A. baumannii. The aim of this research was to substantiate the way of overcoming of resistance in clinical strains of A. baumannii, by means of synergic antimicrobial activity of antibiotics and antiseptic decamethoxinum®. Material and methods. The research was carried out on 190 clinical strains of A. baumannii, isolated from patients with burn disease during the period 2011–2015. The sensitivity of clinical strains of A. baumannii was determined to such antibiotics as ampicillin/sulbactam, cefoperazone, cefoperazone/sulbactam, meropenem, imipenem, amikacin, ciprofloxacin, gatifloxacin and antiseptic decamethoxinum® (DCM; Registration certificate No UA/14444/01/01 since 24.06.2015. Order of the Ministry of Health of Ukraine No 373). The sensitivity of A. baumannii to antibiotics and DCM was determined by means of disk diffusion test and serial dilution (Order of the Ministry of Health of Ukraine No167 since 05.04.2007; EUCAST expert rules).The study of the influence of antiseptic DCM on the sensitivity of acinetobacteria to antibiotics was studied on 35 clinical strains of A. baumannii, drafted from the general number of isolates enrolled in the research. For this, the sensitivity of A. baumannii to antibiotics in the presence of sub-minimal inhibitory concentrations (subMIC) of DCM was identified. The received experimental data were analyzed by “Statistica 6.0”. Results and discussion. The changes of antibiotic sensitivity profile of A. baumannii for five years were shown. It was found that the sensitivity of A. baumannii to majority of antibiotics, selected for study, decreased significantly. But the only ampicillin/sulbactam was found to have vice versa tendency. We found the rising quantity of antibiotic resistant strains of A. baumannii. At the same time, high resistance of acinetobacteria to fluoroquinolones (ciprofloxacin– 96,1%; gatifloxacin– 95,8%) was found in 2015. The in vitro research of combined activity of DCM antiseptic remedy and early mentioned antibiotics against clinical strains of A. baumannii demonstrated the reveal antibiotic effectiveness. As follows, minimal inhibitory concentrations of antibiotics decreased in 1.5–4 times in the mediums which contained subMIC of DCM. Especially this tendency was found in resistant clinical strains. Conclusion. Under selective influence of antibiotics protected by β-lactamase inhibitors, carbapenems, fluoroquinolones aminoglycosides increase the antibiotic resistance in A. baumannii, causative agents of infectious complications in patients with burn disease. The antiseptic remedy decamethoxinum® helps to improve antibiotic sensitivity in resistant A. baumannii.